Linguistic Pluralism and the Shaping of Identity: A Philosophical Examination of Language Policy in Ukrainian Higher Education - Zaichko, Vladyslava (Studia Warmińskie, 2023)
This comprehensive study explores the multifaceted nature of language policy in Ukrainian Higher Education Institutions (HEIs) against the backdrop of increasing globalization and a rising influx of international students. Employing a multi-level methodological approach, the paper analyzes the current state of language policy, emphasizing its role in academic performance, cultural identity, and international competitiveness. The study also investigates the impact of technology on the implementation of these policies, highlighting the potential for digital platforms to amplify or impede educational objectives. Data was collected from a diverse range of institutions and indicates significant room for improvement in existing policies. Recommendations are offered at multiple levels, focusing on enhancing the effectiveness, inclusivity, and cultural sensitivity of language policies. The findings underscore the necessity of an interdisciplinary approach to crafting a language policy that is both academically rigorous and culturally inclusive.